Iluzje oszczędności wydatków publicznych - Piotrowska-Marczak, Krystyna (The Illusion of Economizing on Public Expenditures, 2009)
Financial policy geared to reducing public expenditures is a factor decelerating both economic and social development. To confirm the above statement, the paper provides a range of data showing lower budget outgoings in 2009. Further, it presents Poland's position in a ranking assessing the level of country's development and life quality in relation to the other 26 member states of the European Union
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 224-232